2018
DOI: 10.2147/cia.s153782
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of natural eggshell membrane versus placebo in exercise-induced joint pain, stiffness, and cartilage turnover in healthy, postmenopausal women

Abstract: PurposeDespite its many health benefits, moderate exercise can induce joint discomfort when done infrequently or too intensely even in individuals with healthy joints. This study was designed to evaluate whether NEM® (natural eggshell membrane) would reduce exercise-induced cartilage turnover or alleviate joint pain or stiffness, either directly following exercise or 12 hours post exercise, versus placebo.Patients and methodsSixty healthy, postmenopausal women were randomly assigned to receive either oral NEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…The presence of this multitude of components makes the eggshell membrane an ideal candidate as biomaterial for tissue engineering applications, and specifically for the connective tissue repair. In particular, as a dietary supplement, the eggshell membrane has been proved effective in the treatment of joint‐pain and cartilage turnover, but it was rarely used as a starting material for the production of cartilage scaffold (Adali et al., 2019; NCT03769857, 2018; Pillai et al., 2015; Ruff et al., 2018). Proteins from membrane can be easily extracted and then processed to produce eggshell membrane‐based materials (Long et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of this multitude of components makes the eggshell membrane an ideal candidate as biomaterial for tissue engineering applications, and specifically for the connective tissue repair. In particular, as a dietary supplement, the eggshell membrane has been proved effective in the treatment of joint‐pain and cartilage turnover, but it was rarely used as a starting material for the production of cartilage scaffold (Adali et al., 2019; NCT03769857, 2018; Pillai et al., 2015; Ruff et al., 2018). Proteins from membrane can be easily extracted and then processed to produce eggshell membrane‐based materials (Long et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies have demonstrated that EM leads to a reduction in the production of pro-inflammatory cytokines, such as interleukin-1 beta and tumor necrosis factor-alpha both in vitro 14 and in vivo . 15 EM has been shown to improve recovery from exercise-induced joint pain (day 8), decrease stiffness (day 4), and reduce discomfort immediately after exercise (stiffness, day 7) in postmenopausal women taking 500 mg once daily for 2 weeks. In the same study, a decrease in the cartilage degradation biomarker CTX-II occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include hyaluronan, chondroitin, dermatan, heparin/heparan, and keratan, some of which have been shown to benefit joint health in multiple studies. 9–11,13,15–18…”
Section: Introductionmentioning
confidence: 99%
“…Prior multiple published studies have not reported any safety concerns or adverse events. Those with an allergy to egg or egg products should not consume eggshell membrane …”
Section: Resultsmentioning
confidence: 99%